2010
DOI: 10.1021/la101012a
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Structures and pKa Value of Oleic Acid in Systems of Biological Relevance

Abstract: In the human digestion process, triglycerides are hydrolyzed by lipases to monoglycerides and the corresponding fatty acids. Here we report the self-assembly of structures in biologically relevant, emulsified oleic acid-monoolein mixtures at various pH values and oleic acid concentrations. Small-angle X-ray scattering, cryogenic transmission electron microscopy, and dynamic light scattering were used to investigate the structures formed, and to follow their transitions while these factors were varied. The addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
227
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 198 publications
(244 citation statements)
references
References 61 publications
17
227
0
Order By: Relevance
“…The magnitude of adhesion between the membranes was 0.6 ± 0.1 mN/m and no electrostatic repulsion was observed. The lack of electrostatic repulsion is consistent with a very low-degree of deprotonated oleic acid at pH of 5.8 (pKa of oleic acid N 6.1) [24].…”
Section: Monolayer Properties Of Dppc-oleic Acid Mixturessupporting
confidence: 61%
See 2 more Smart Citations
“…The magnitude of adhesion between the membranes was 0.6 ± 0.1 mN/m and no electrostatic repulsion was observed. The lack of electrostatic repulsion is consistent with a very low-degree of deprotonated oleic acid at pH of 5.8 (pKa of oleic acid N 6.1) [24].…”
Section: Monolayer Properties Of Dppc-oleic Acid Mixturessupporting
confidence: 61%
“…For example, the pKa of pure oleic acid vesicles is 8.0- 9.5 [27,42,43]. While when mixed with monoolein, the pKa was 6.0-7.0 [24]. A similar pKa of 6.5 was found for 4:6 oleic acid-DPPE vesicles [25].…”
Section: Dissociation Of Oleic Acid In Mixed 7:3 Dppc-oleic Acid Membmentioning
confidence: 66%
See 1 more Smart Citation
“…15 Therefore, in alkaline aqueous solutions (pH 7-10), fatty-acid assemblies are composed of two types of amphiphiles: a neutral carboxylic acid form and a carboxylate anion form. [16][17][18][19] The higher pK a app values of assembled fatty acids are due to the interaction between carboxylates 14,15,17 and the characteristic dielectric properties and proton activities around the self-assembly surface. 17 These properties change temporally during the nonequilibrium self-assembly process; thus, the acid dissociation of fatty acids fluctuates greatly.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] The higher pK a app values of assembled fatty acids are due to the interaction between carboxylates 14,15,17 and the characteristic dielectric properties and proton activities around the self-assembly surface. 17 These properties change temporally during the nonequilibrium self-assembly process; thus, the acid dissociation of fatty acids fluctuates greatly. For instance, Sugawara et al reported that several 10 micrometer-sized helical assemblies of oleates in aqueous solution showed spontaneous winding-rewinding motions during helical structure formation, probably owing to fluctuation of the ratio of neutral oleic acid to oleate anion in the assembly.…”
Section: Introductionmentioning
confidence: 99%